Risk Factors for of Urinary Tract Infection in Catheter Installation in Hospitals - Kusbaryanto Kusbaryanto; Listiowati Listiowati (Universitas Muhammadiyah Yogyakarta, 2021)
CAUTI has been shown to increase the mortality rate, length of stay (LOS), susceptible patients to CAUTI are due to risk factors, namely women, the elderly, and diabetics. This study aimed to analyze the risk factors for the Incidence of urinary tract infections in patients with catheters in Hospitals. The research design used was an observational analytic study with a cross sectional design approach. The sample in this study were patients diagnosed with UTI in the inpatient room for 4 months from November 2019 to February 2020, obtained as many as 11 respondents with inclusion criteria being patients diagnosed with clinical urinary tract infection and having a catheter installed for at least 3 days. Sample selection is done by Consecutive Sampling. Data were taken from medical records at the hospital. Ethical permission for this research was granted from the research ethics section of Aisyiyah University Yogyakarta. There are three results of the analysis, namely: 1) gender has an effect on UTI (p = 0.023), the female gender is 7 times more at risk than the male gender (OR = 7.041), 2. age affects UTI (p = 0.004), age more than 70 years old is 11 times more likely to have UTI compared to those less than 70 years old (OR = 11,445), 3. Age factor is more influential on UTI than gender. The risk factors for the incidence of urinary tract infections in patients with catheters in the hospital are: 1. Gender, female sex is 7 times more at risk than male sex, 2. Age, over 70 years old is 11 times more at risk of UTI compared to those aged less than 70 years.